Microalgae culture training as an effort to improve natural feed quality for shrimp seed cultivation of Benur Barokah Group - Sulastri Arsad; Muhammad Musa; Evellin Dewi Lusiana; Mohammad Mahmudi; Siti Nurchotipah; Nur Aliya Nabila Zsalzsabil; Rafli Wildan Ramadiansyah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
The Community Partnership Program (PKM) aims to conduct training on microalgae culture and water quality management in aquaculture ponds as an effort to improve the quality of natural feed for shrimp seeds. This activity was carried out in the Tuban Barokah Benur group in 2021. A cultivation experiment of three types of microalgae was carried out and the species was given as a natural feed for shrimp seeds. Microalgae Tetraselmis sp., Dunaliella sp., and Chlorella sp. were cultured for 7 days and tested as shrimp seed feed. The results showed that the percentage of survival of shrimp seed was highest in the containers given byTetraselmis sp. (32%). Furthermore, microalgae culture assistance activities in the Benur Barokah group used the microalgae Tetraselmis sp. carried out in Situ on a small scale. In addition, water quality tool measurement is also provided to help monitor the water quality of the tank regularly. The questionnaire results showed a positive response to training activities from Benur Barokah partners covering six aspects with a good response of 50-90%.